2017
DOI: 10.1038/srep44200
|View full text |Cite
|
Sign up to set email alerts
|

Historical range, extirpation and prospects for reintroduction of saigas in China

Abstract: An assessment of historical distribution patterns and potential reintroduction sites is important for reducing the risk of reintroduction failure of endangered species. The saiga antelope, Saiga tatarica, was extirpated in the mid-20th century in China. A captive population was established in the Wuwei Endangered Wildlife Breeding Centre (WEWBC) in the 1980s. Reintroduction is planned, but so far, no action has been taken. In this study, we delineated the historical distribution and potential reintroduction ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In 2018 in Xinjiang the 3 parallel border separation fences were built (Liu et al, 2020), which severely restricted the transboundary migration of wildlife and grazing of livestock, and to some extent, it is beneficial to the control the spreading of PPR (Cui et al, 2017). However, from the experience of the construction and lesson of damaging of the border fences in northeast border of China, it is impossible to build a large-scale border separation fences without any escape intervals for wildlife, even in the hilly and plain areas such as the northeastern China; secondly, in some special environments, such as rivers which can not be completely enclosed and remain for wildlife migration; Finally, the capability to damage fences of wild animals can not be ignored, such as the usual seen damage of boar to the border fences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018 in Xinjiang the 3 parallel border separation fences were built (Liu et al, 2020), which severely restricted the transboundary migration of wildlife and grazing of livestock, and to some extent, it is beneficial to the control the spreading of PPR (Cui et al, 2017). However, from the experience of the construction and lesson of damaging of the border fences in northeast border of China, it is impossible to build a large-scale border separation fences without any escape intervals for wildlife, even in the hilly and plain areas such as the northeastern China; secondly, in some special environments, such as rivers which can not be completely enclosed and remain for wildlife migration; Finally, the capability to damage fences of wild animals can not be ignored, such as the usual seen damage of boar to the border fences.…”
Section: Discussionmentioning
confidence: 99%
“…Planting and animal husbandry are the main local production mode, and there are bilateral cross-border grazing. It has been reported that Saiga antelopes which widely distributed in Kazakhstan migrates to the north and south twice a year, and they migrate to Xinjiang, China through Kazakhstan to give birth, which also provides the possibility for PPR cross-border transmission (Cui et al, 2017, Bekenov et al, 2010. The cross-border paths a.b.c enters China from the west of Pamir Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Boshoff, Kerley et al [12,13] used the historical occurrences and ecological requirements of 42 medium-to large-sized mammals to estimate their potential distributions. Cui, Milnergulland et al [14] focused on the assessment of the historical distribution and migration patterns of the saiga antelope, Saiga tatarica, to determine potential reintroduction sites.…”
Section: Introductionmentioning
confidence: 99%
“…The reintroduction of species to areas from which they have been historically extirpated is an increasingly relevant conservation tool (Seddon, Griffiths, Soorae, & Armstrong, 2014). Studies that evaluate the success of such introductions from different vantage points (socio-economic, ecological and biological) are therefore essential (Cui et al, 2017;Seddon et al, 2014). Elephants are charismatic, long-lived, socially complex and ecologically influential.…”
Section: Introductionmentioning
confidence: 99%